1965
DOI: 10.1152/ajplegacy.1965.209.4.699
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial potassium balance during cardioaccelerator nerve and atrial stimulation

Abstract: By following changes in arterial-coronary sinus plasma potassium concentration differences, the myocardial potassium balance was studied during the increased heart rate produced by cardioaccelerator nerve or right atrial stimulation. With cardioaccelerator nerve stimulation there was an initial loss of myocardial potassium of brief duration, followed by an uptake for the duration of the stimulation. Atrial stimulation leads predominantly to a loss of myocardial potassium, particularly when the reflex effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1967
1967
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Consistent with this hypothesis, subsequent studies found K + to be a vasodilator (131, 267, 373, 701) and myocardial efflux of K + to be elevated by tachycardia (374, 375, 411, 751, 897, 975, 986) and myocardial ischemia (150,162,211,375,440,510,751,846). However, the vasodilator action of K + has been shown to be transient (131, 373), and higher concentrations of K + (typically > 20 mmol/L) are known to produce vasoconstriction (875).…”
Section: Metabolic Control Of Coronary Blood Flowmentioning
confidence: 70%
“…Consistent with this hypothesis, subsequent studies found K + to be a vasodilator (131, 267, 373, 701) and myocardial efflux of K + to be elevated by tachycardia (374, 375, 411, 751, 897, 975, 986) and myocardial ischemia (150,162,211,375,440,510,751,846). However, the vasodilator action of K + has been shown to be transient (131, 373), and higher concentrations of K + (typically > 20 mmol/L) are known to produce vasoconstriction (875).…”
Section: Metabolic Control Of Coronary Blood Flowmentioning
confidence: 70%
“…Potassium is a coronary vasodilator over a certain concentration range (Cohen, 1936;Katz and Lindner, 1938;Driscol and Berne, 1958;Scott et al, 1961;Konold et al, 1967;Norton and Detar, 1972;Gellai and Detar, 1974;Bunger et aL, 1976;Murray and Sparks, 1978), although its vasodilator action may be only transitory (Gellai and Detar, 1974;Bunger et al, 1976). Potassium efflux from myocardium is enhanced by increases in heart rate (Wilde, 1957;Wood and Conn, 1958;Sybers et al, 1965;Langer and Brady, 1966;Grupp et al, 1967;Gilmore and Gerlings, 1969;Parker et al, 1970) and by limitations of oxygen supply (Cherbakoff et al, 1957;Harris et al, 1958;Cummings, 1960;Jennings et al, 1964;Parker et al, 1970;Case, 1971;Scott and Radawski, 1971). Driscol and Berne (1958) failed to find a steady state correlation between myocardial K + loss and coronary blood flow.…”
mentioning
confidence: 99%
“…In this study we have investigated these possibilities. More specifically, we have attempted to determine whether the mechanism of K + -induced coronary vasodilation involves: (1) a primary increase in the metabolic activity of the heart, (2) an increased release of norepinephrine from sympathetic nerve terminals in the heart, (3) an increased release of acetylcholine from parasympathetic nerve terminals in the heart, (4) a withdrawal of a-adrenergic-mediated coronary vascular smooth muscle tone, or (5) an activation of the electrogenic Na + -K + transport system of coronary vascular smooth muscle. …”
mentioning
confidence: 99%